Pelaksanaan Perjanjian Kemitraan Antara PT. GRAB Dengan Ritel Makanan: (Studi Di Kota Mataram) - Khaezul Fikri; Eka Jaya Subadi (Fakultas Hukum Universitas Mataram, 2022)
This study describes the implementation procedure of partnership agreement between PT. Grab and food vendors, and identifies the solution in the case of default. This study is a normative-empirical one. The partnership between PT. Grab and food vendors is written in agreements. Agreement points are submitted electronically. Rights and obligations for both parties are managed in Article 5.1 and 5.2 regarding requirements and general provisions in Grab App. In the case of default, both parties agree to undertake colloquial negotiation, considering social and customary law.